The Role of Ultrasound in Detecting Residual or Recurrent Breast Carcinoma: A Case Report of a Patient Following Wide Excision in the Contralateral Breast - Andini Sangkal; Rahmawati Rahmawati; Pither Sandy Tulak (Journal of Community Health Provision, 2026)
Breast carcinoma represents the most prevalent malignancy among women, rendering routine surveillance using ultrasonography (USG) essential for early detection and monitoring. This case report describes a 49-year-old female presenting with a palpable mass and pain in the left breast, occurring one year after undergoing wide excision in the right breast, with prior histopathological findings of microglandular adenosis. Physical examination revealed bilateral breast masses without evidence of axillary lymphadenopathy. Breast ultrasonography demonstrated a cystic lesion with a solid component in the right breast and a cystic lesion in the left breast, both classified as BI-RADS III. This case underscores the critical role of post–wide excision surveillance using ultrasonography in identifying residual or recurrent lesions in the breast, including the contralateral side. Consistent monitoring and an appropriate clinical approach are expected to prevent diagnostic delays and improve clinical outcomes in patients with residual or recurrent breast lesions.